2018
DOI: 10.1007/s10142-018-0595-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics analysis revealing candidate networks and genes for the body size sexual dimorphism of Chinese tongue sole (Cynoglossus semilaevis)

Abstract: The Chinese tongue sole (Cynoglossus semilaevis) is a typical female heterogamete species that exhibits female-biased sexual size dimorphism, which has severely hindered the sustainable development of the species in aquaculture. In the present study, four important somatotropic and reproductive tissues including brain, pituitary, liver, and gonad from 15 females and 15 males were used for transcriptome analysis via RNA-seq. A mean of 37,533,991 high-quality clean reads was obtained from each library and 806, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 62 publications
5
48
0
Order By: Relevance
“…Primers ( Table S1 ) were designed based on sequences from the National Center for Biotechnology Information (NCBI) database. β-actin gene was used as the internal control (Wang et al, 2018). One microgram total RNAs for high-throughput transcriptome sequencing was reverse transcribed into cDNA with the PrimeScript ™ RT reagent Kit with gDNA Eraser (Takara, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers ( Table S1 ) were designed based on sequences from the National Center for Biotechnology Information (NCBI) database. β-actin gene was used as the internal control (Wang et al, 2018). One microgram total RNAs for high-throughput transcriptome sequencing was reverse transcribed into cDNA with the PrimeScript ™ RT reagent Kit with gDNA Eraser (Takara, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies identified genes related to sexual dimorphism through transcriptome analysis of adult C . semilaevis (Guo et al, 2016; Wang et al, 2018; Liu et al, 2019). Gene expression patterns in the gonads of C .…”
Section: Introductionmentioning
confidence: 99%
“…To gain insight into the molecular mechanisms underlying female-superior sexual dimorphism with respect to growth rate, WGCNA analysis of female banana shrimp ( Fenneropenaeus merguiensis ) digestive gland tissue samples was completed by Powell et al and revealed a gene module containing a large number of transcripts with homology to transcription factors and genes associated with growth regulation [13]. Wang et al found two gene modules (yellowgreen and salmon4) that were significantly positively correlated with female-biased sexual size dimorphism using WGCNA, and identified a series of hub genes by drawing an illustrated network map of these two modules in Chinese tongue sole ( Cynoglossus semilaevis ) [14].…”
Section: Introductionmentioning
confidence: 99%
“…The normalized (screened for missing values) gene expression matrix was imported into WGCNA to construct co-expression modules. Gene expression matrix was searched for a suitable soft threshold for building gene networks using a scale-free topology model [56]. After a threshold lter, the nal selection is β = 22.…”
Section: Construction Of the Weighted Gene Co-expression Networkmentioning
confidence: 99%